Trichodysplasia spinulosa: a comprehensive review of the disease and its treatment. (6th January 2021) - Curman, P.; Näsman, A.; Brauner, H.
Abstract: Trichodysplasia spinulosa (TS) is a rare dermatological disease caused by TS‐associated polyomavirus (TSPyV) in immunosuppressed patients. The seroprevalence of TSPyV in immunocompetent adults is high and the number of immunosuppressed patients developing TS remains low, suggesting that TS is underdiagnosed and/or that additional unknown factors are needed in order to develop TS. There is no well‐established treatment for TS, and to date a majority of reported cases have consequently received ineffective therapies, likely due to the unavailability of reviews and recommendations of treatments for TS. The few treatments reported in case reports to be effective include topical cidofovir 3%, reduction of immunosuppression and oral valganciclovir. In this comprehensive review, we present all published cases to date, together with a summary of all treatments for TS categorized by overall clinical efficacy, thus addressing this rare disease and what appears to be its clinically efficacious treatment.